Effects of whole-body electromyostimulation on chronic nonspecific low back pain in adults: a randomized controlled study - Weißenfels, Anja; Teschler, Marc; Willert, Sebastian; Hettchen, Michael; Froehlich, Michael; Kleinoeder, Heinz; Kohl, Matthias; von Stengel, Simon; Kemmler, Wolfgang (Journal of Pain Research, 2018)
Purpose: Low back pain (LBP) is one of the most frequent chronic conditions worldwide. Data from a recent meta-analysis indicated that whole-body electromyostimulation (WB-EMS), a time-effective, joint-friendly, and highly individualized training technology, demonstrated promising effects on LBP; however, methodologic limitations prevent definitive evidence for this result. Thus, the aim of this study was to conduct a randomized controlled WB-EMS trial to determine the corresponding effect on chronic, nonspecific LBP in people with chronic LBP. Patients and methods: Thirty LBP patients, 40-70 years old, were randomly assigned into two groups (WB-EMS: 15; control [CG]: 15). While the nonactive CG maintained their lifestyle, the WB-EMS group completed a 12-week WB-EMS protocol (1×20 min/week) with slight movements, specifically dedicated to LBP. Pain intensity and frequency were determined by a 4-week pain diary before and during the last 4 weeks of intervention. Primary study endpoint was average pain intensity at the lumbar spine. Results: At baseline, no group differences apart from nonregular exercise were observed. Mean intensity of LBP decreased significantly in the WB-EMS group (P=0.002) and remained unchanged in the CG (P=0.730), with a significant difference between both groups (P=0.027). Maximum isometric trunk extensors improved significantly in the WB-EMS group (P=0.005), while no significant difference was seen in the CG (P=0.683). In contrast to the significant difference between WB-EMS group and CG for the latter parameter (P=0.038), no intergroup difference was determined for maximum isometric trunk flexors (P=0.091). The WB-EMS group showed a significant increase of this parameter (P=0.003), while no significant change was determined in the CG (P=0.563). Conclusion: WB-EMS is a time-effective training method for reducing chronic nonspecific LBP and increasing maximum trunk strength in people with such complaints. After this promising comparison with a nonactive CG, research needs to be extended to include comparisons with active groups (WB-Vibration, conventional back strengthening).
EVALuna2:214339